2011
DOI: 10.1111/j.1526-4637.2010.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinic Group Education Sessions Reduce Waiting Times and Costs at Public Pain Medicine Units

Abstract: The introduction of STEPS was associated with reduced wait-times and costs at public pain medicine units and increased both the use of active pain management strategies and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 40 publications
(43 reference statements)
3
80
1
Order By: Relevance
“…For example, although an earlier review identified limited implementation of health policy into practice for osteoarthritis in Australia, 16 this situation is slowly being redressed with the introduction of MoCs, in this context particularly through the NSW MoC for osteoarthritis and WA MoC for Elective Joint Replacement (Table 1). Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…For example, although an earlier review identified limited implementation of health policy into practice for osteoarthritis in Australia, 16 this situation is slowly being redressed with the introduction of MoCs, in this context particularly through the NSW MoC for osteoarthritis and WA MoC for Elective Joint Replacement (Table 1). Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Using a system inversion MoSD, aligned with an MoC in Western Australia, inter-professional consumer group education sessions delivered prior to face-to-face practitioner appointments have resulted in significantly reduced wait-times and costs at public pain medicine units [22]. Further, consumer use of active pain self-management strategies increased with fewer requiring individual consultations.…”
Section: Health System Inversion As An Implementation Enablermentioning
confidence: 99%
“…Further, consumer use of active pain self-management strategies increased with fewer requiring individual consultations. This MoSD is recurrently resourced and has now been adopted in a number of primary care sites throughout Australia [22].…”
Section: Health System Inversion As An Implementation Enablermentioning
confidence: 99%
See 1 more Smart Citation
“…A growing trend in healthcare, owing to spiralling costs and the shortage of providers, is an emphasis on self-management strategies or group education sessions for patients with chronic medical conditions 12,13 . This is very different from the traditional treatment model centred around doctor/patient clinic visits.…”
Section: Current Treatment Of Chronic Painmentioning
confidence: 99%